Countering Islamophobia through Sports: Qatar’s Initiatives during the 2022 FIFA World Cup - Ismail, Mustafa Osman (International Journal of Membrane Science and Technology, 2023)
This paper examines how Qatar used the 2022 FIFA World Cup as a platform to address global Islamophobia. Taking place in the context of a conference on Islamophobia at Georgetown University in Qatar, the study analyzes the role Western media played in reinforcing negative stereotypes and biases against Muslims before and during the event. It highlights Qatar’s wide-ranging efforts to educate the public, influence policy, and promote open discussions on how to counteract these prejudices. Special attention is given to the significant role of sports celebrities, particularly football star Mo Salah, in reducing anti-Muslim sentiment. Empirical data support the idea that Salah’s public Muslim identity contributed to a decline in hate crimes and negative social media chatter. Additionally, the study explores the possible positive impact, known as the "Qatar effect," that hosting the World Cup could have on reducing negative attitudes towards Muslims. This is similar to how Mo Salah’s presence and influence have positively affected public opinion, known as the "Salah effect." The paper also discusses how Qatar infused cultural elements, like Quranic verses and Bedouin traditions, into the event to foster a broader understanding and appreciation of its heritage. It further addresses ethical and human rights concerns such as the conditions of migrant workers and civil liberties, emphasizing the inconsistency in how the world reacts to these issues in different contexts. Overall, this research offers a comprehensive look at how the 2022 FIFA World Cup served as a stage for Qatar to influence global perspectives on Islamophobia while shedding light on the social and political complexities tied to hosting a world-renowned event.